Like father, like son: does migration experienced during child schooling affect mobility?. Issue 45 (26th September 2022) - Sharma, Swati; Dubey, Amaresh
ABSTRACT: Using a sample of 39, 297 father-son pairs from Indian Human Development Surveys (IHDS), we examine whether migration experienced during child schooling affects the relationship between parent and child education. We relax the co-residency restriction for father-son pairs to obviate coresident sample selection bias in our mobility estimates. The panel structure of data enables us to identify children who were enrolled in school at the time when their families migrated. We find that migration experienced during schooling increases downward mobility. In particular, those children who were young at the time of migration tend to have poor educational outcomes. We show that widely cited aggregate measures of mobility provide an incomplete representation of intergenerational persistence in India, as most of the persistence originates from the tails of the educational distribution. The sons of the least educated fathers have poor prospects of upward mobility and face a glass ceiling in higher education. We use heteroscedasticity-based identification and Rosenbaumʻs sensitivity analysis to account for unobserved heterogeneity.